2015
DOI: 10.1016/j.bbamcr.2014.12.012
|View full text |Cite
|
Sign up to set email alerts
|

ANKHD1 silencing inhibits Stathmin 1 activity, cell proliferation and migration of leukemia cells

Abstract: ANKHD1 is highly expressed in human acute leukemia cells and potentially regulates multiple cellular functions through its ankyrin-repeat domains. In order to identify interaction partners of the ANKHD1 protein and its role in leukemia cells, we performed a yeast two-hybrid system screen and identified SIVA, a cellular protein known to be involved in proapoptotic signaling pathways. The interaction between ANKHD1 and SIVA was confirmed by co-imunoprecipitation assays. Using human leukemia cell models and lenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 44 publications
3
31
0
Order By: Relevance
“…Hence, it was hypothesized that ANKHD1 may play a role in NSCLC progression. Previous studies reported that ANKHD1 was highly expressed in a leukemic cell line, prostate cancer cells and myeloma cells (7,20,(26)(27)(28). Similarly, our data demonstrated that the ANKHD1 mRNA and protein levels were also significantly upregulated in NSCLC cells.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Hence, it was hypothesized that ANKHD1 may play a role in NSCLC progression. Previous studies reported that ANKHD1 was highly expressed in a leukemic cell line, prostate cancer cells and myeloma cells (7,20,(26)(27)(28). Similarly, our data demonstrated that the ANKHD1 mRNA and protein levels were also significantly upregulated in NSCLC cells.…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies have demonstrated that the ANKHD1 protein is highly expressed in the stomach, small intestine and liver, but its expression is low in the spleen, lung and kidney (7). Furthermore, the expression of ANKHD1 is high in the blood cells of patients with multiple myeloma and leukemia (7,20,(26)(27)(28). However, only few studies have investigated the role of ANKHD1 in solid cancers to date (21).…”
Section: Discussionmentioning
confidence: 99%
“…At present, Siva 1 is pro-apoptotic and carcinostatic in colorectal (14), cervical (5) and breast cancer (12) and acute leukemia (15), but anti-apoptotic and carcinogenic in osteosarcoma (11) and NSCLC (9). However, it remains unknown whether Siva 1 functions in ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%
“…They interacted with YAP to regulate Hippo pathway 11, 12. Mask1 (or ANKHD1) played an important role in cancer cell growth, such as prostate cancer, myeloma and leukemia cells 13-18. However, the cellular behavior or mechanisms of Mask2 (or ANKRD17) in cancer cells was unknown, although Mask2 was reported to involve in immune signaling 19.…”
Section: Introductionmentioning
confidence: 99%